Analysis of latent class and influencing factors of medication adherence in elderly patients with multiple chronic conditions - Zhang Meiru; Ma Lina; Yang Shenshen; Wang Ning; Wang Weihua (Guoji laonian yixue zazhi)
[Objective] To explore the latent class and influencing factors of medication compliance in the elderly with multiple chronic conditions. [Methods] From March to September 2023, the elderly people aged ≥60 years old were selected from two community medical institutions in Beijing by convenience sampling method. Data were collected using the General Information Questionnaire, the Chinese version of 8-item Morisky medication adherence scale, the Chinese version of the medication beliefs about medication questionnairee-specifie, and the frailty assessment scale. The latent class analysis method was used to classify and name the medication compliance of the elderly with chronic multiple chronic condition comorbidities. Multiple logistic regression model was used to analyze the influencing factors of the potential category. [Results] 340 questionnaires were distributed, 23 invalid questionnaires were removed, and 317 valid questionnaires were collected.Through latent class analysis. 317 elderly patients with multiple chronic conditions were divided into 3 categories: poor overall medication compliance group, poor subjective medication compliance group, and good overall medication compliance group. There were statistically significant differences among the 3 groups in education level, place of residence, annual total income, type of payment, attention to popular science public accounts, daily time of medication, stages of weakness and belief in medication (P < 0.05). The results of multiple logistic regression analysis showed that education level, payment type, debilitation stage, belief level of taking medicine and attention paid by popular science public accounts were the influential factors for medication compliance of the elderly with multiple chronic conditions (P < 0.05). [Conclusion] The medication compliance of the elderly with multiple chronic conditions needs to be improved, and the clinical staff should conduct individualized intervention according to the category characteristics of medication compliance.